주요 스프레이 국화 품종의 형태적 특성과 변이계수, 유전율 및 유전자 전이율 - 심성임(Sung-Im Shim); 임기병(Ki-Byung Lim); 김창길(Chang-Kil Kim); 정미영(Mi-Young Chung); 김경민(Kyung-Min Kim); 정재동(Jae-Dong Chung) (Weon'ye gwahag gi'sulji, 2016)
The statistical analyses of coefficient of variation, heritability, and genetic advance were carried out to identify differences in morphological characteristics, such as the stem and inflorescence length, of 10 major commercial cultivars of spray chrysanthemum (Chrysanthemum morifolium). For morphological characteristics, stem lengths ranged from 46.4 cm to 54.9 cm, the maximum diameter of stem was 5.6 to 8.5 mm, the hardness of the stem was 0.17 to $0.70kg{·}m^{-2}$, the fresh weight of stem was 7.5 to 17.5 g, the dry weight of the stem was 1.6 to 3.3 g, the ratio of dry weight/fresh weight of stem was 15.9% to 23.1%. Also, the number of leaves on the stem was 8.4 to 12.2, the stem leaf area was 17.8 to $37.8m^2$, the fresh weight stem leaves was 5.3 to 18.6 g, the dry weight was 0.5 to 1.4 g and the ratio of dry weight /fresh weight of stem leaves was 7.6% to 11.5%. The inflorescence length ranged from 10.1 to 18.6 cm, the fresh weight of inflorescence was 7.3 to 26.7 g, the dry weight of inflorescence was 1.2 to 2.8 g, the ratio of dry weight /fresh weight of inflorescence was 10.4% to 17.1%. For flower, the diameter of the flower center was 8.2 to 13.3 mm, the petal width was 5.7 to 14.0 mm, the petal length was 12.9 to 33.1 mm, and the petal thickness was 157.8 to $354.4μm$. The mean values of each character in each cultivar were very different, and DMRT and LSD values based on morphological characteristics among 10 cultivars were highly significant. For variability and genetic parameters, the lowest CV (coefficient of variation), PCV (phenotypic coefficient of variation), and GCV (genotypic coefficient of variation) were 4.79% to 5.15% in stem length, and the highest variations were 62.97% to 65.21% in leaf area. ECV (error or environmental coefficient of variation) was the lowest for leaf area (1.71%) and it was the highest for leaf dry weight (19.30%). Heritability also significantly differed among the characteristics, ranging from 68.69% to 99.67%, the lowest value was shown in ratio of dry weight /fresh weight of stem and the highest value was for leaf area of stem. The value for genetic advance was the lowest in hardness of stem at 0.30 and the highest in leaf thickness at 156.65. The lowest genetic advance as percentage of mean of stem hardness was 9.17%, while the highest percentage of stem length was 134.27%. Thus the characters which had the highest values indicated above show the influence of additive gene action and may provide useful resources for selection programs for agronomic improvement. 절화용으로 재배중인 주요 스프레이 국화 10품종의 형태적 특성과 관련된 요인을 조사하였으며 이들 평균치를 이용하여 변이계수, 유전율 및 유전자 전이율 등의 통계학적 분석을 통하여 얻은 결과를 요약하면 다음과 같다. 형태적 특성을 보면 줄기의 길이 46.4-54,9cm, 줄기의 최대 직경 5.6-8.5mm, 줄기의 경도 $0.17-0.70kg{·}m^{-2}$, 줄기의 생체중 7.5-17.5g, 줄기의 건물중 1.6-3.3g, 줄기의 생체중:건물중의 비율 15.9-23.1%, 줄기 내 엽수 8.4-12.2매, 줄기 내 엽면적 $17.8-37.8m^2$, 줄기 내 잎의 생체중 5.3-18.6g, 줄기 내 잎의 건물중 0.5-1.4g 줄기 내 잎의 생체중:건물중의 비율 7.6-11.5%, 화서의 길이 10.1-18.6cm, 화서의 생체중 7.3-26.7g, 화서의 건물중 1.2-2.8g, 화서의 생체중:건물중의 비율 10.4-17.1%, 화심 직경 8.2-13.3mm, 꽃잎 폭 5.7-14.0mm, 꽃잎 길이 12.9-33.1mm, 꽃잎 두께 $157.8-354.4μm$였으며 각 특성별 품종 간 DMRT와 LSD를 검정한 결과 고도의 유의차가 인정되었다. 변이계수, 표현 변이계수, 유전 변이계수는 줄기의 길이 4.79-5.15%로서 가장 낮았으며 엽면적 62.97-65.21%로 가장 높았으나 환경 또는 오차 변이계수는 엽면적 1.71%로 가장 낮았고 잎의 건물중 19.30%로 가장 높았다. 유전율은 줄기의 생체중:건물중의 비율 68.69%로 가장 낮았고 줄기 내 엽면적 99.67%로 가장 높았다. 유전자 전이는 줄기의 경도 0.30으로 가장 낮았고 화서 내 잎의 두께 156.65로 가장 높았으며 유전자 전이율은 줄기의 길이 9.17%로 가장 낮았으며 엽면적 134.27%로 가장 높았다. 이와 같이 위에서 언급한 높은 값을 나타내는 형질들은 부가적으로 유전자 작용에 영향을 미치게 되며 경종의 개량을 위해 만족할만한 선발 계획을 수립할 수 있을 것이다.